2011
DOI: 10.1126/science.1213272
|View full text |Cite
|
Sign up to set email alerts
|

High Relatedness Is Necessary and Sufficient to Maintain Multicellularity in Dictyostelium

Abstract: Most complex multicellular organisms develop clonally from a single cell. This should limit conflicts between cell lineages that could threaten the extensive cooperation of cells within multicellular bodies. Cellular composition can be manipulated in the social amoeba Dictyostelium discoideum, which allows us to test and confirm the two key predictions of this theory. Experimental evolution at low relatedness favored cheating mutants that could destroy multicellular development. However, under high relatedness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
179
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(184 citation statements)
references
References 29 publications
0
179
0
Order By: Relevance
“…Kin selection theory predicts that cooperative behaviours will be selected if relatives preferentially interact with one another by kin recognition or high population viscosity [3][4][5]. High relatedness is key to kin selection and has been shown in social insects [6,7], birds [8,9], mammals [10,11] and microbes [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Kin selection theory predicts that cooperative behaviours will be selected if relatives preferentially interact with one another by kin recognition or high population viscosity [3][4][5]. High relatedness is key to kin selection and has been shown in social insects [6,7], birds [8,9], mammals [10,11] and microbes [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most similar study to those we propose was a recent study of the social amoeba Dictyostelium discoideum [23]. These amoebas, when starved, aggregate and form fruiting bodies in which about 20 per cent of cells altruistically form a somatic stalk that enhances the dispersal of the remaining 80 per cent, which differentiate as reproductive spores [24].…”
Section: Past Experimentsmentioning
confidence: 80%
“…The corresponding experiments with structured reproduction and/or structured growth (figure 1a-c) have not been done, but a separate mutation accumulation experiment showed that the mutation rate to these parasitic cheaters is low [23]. This allowed a calculation that single-cell bottlenecks would generally be sufficient to keep these cheaters from increasing significantly, not just for the plate-sized pseudo-organisms, but also for pseudo-organisms as large as a blue whale.…”
Section: Past Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These non-clonal groups have evolved only relatively limited division of labour, and never complex multicellular organisms (Fisher et al 2013). Numerous experimental studies have shown that this is because in non-clonal groups non-cooperative 'cheats' can spread, limiting the extent of cooperation (Griffin et al 2004;Diggle et al 2007;Kuzdzal-Fick et al 2011;Rumbaugh et al 2012;Pollitt et al 2014;Popat et al 2015;Inglis et al 2017).…”
Section: What Conditions Drive Major Transitions?mentioning
confidence: 99%